Transformasi Proses Penjualan dan Distribusi Melalui Solusi Digital Berbasis Web Pada Perusahaan Fashion - Radithya Saputra; Ririn Ikana Desanti; David Tjahjana (Universitas Islam Raden Rahmat, Malang, 2024)
Digital technology is an integral part of the industrial era 4.0. Every industrial sector must employ technology to stay competitive. This research uses a case study from the CV DV Star company, which operates in the fashion industry. This company is beginning to require an integrated sales and distribution process in order to minimize human error. We propose to build a web-based information system for the sales and distribution process, which will enable users to manage data digitally, eliminating the need for paper-based. This system will cover inventory management, selling transactions, production process, and the reporting process. The system will be designed using the UML modeling language such as use case diagrams and activity diagrams. The method used to develop the system is prototyping. In the end, this web-based information system was implemented in the company.